Proceedings of the International Field Exploration and Development Conference 2017 - Qu, Zhan; Lin, Jia'en (Springer Series in Geomechanics and Geoengineering,, 2019)
This book presents selected papers from the 7th International Field Exploration and Development Conference (IFEDC 2017), which focus on upstream technologies used in oil & gas development, the principles of the process, and various design technologies. The conference not only provides a platform for exchanging lessons learned, but also promotes the development of scientific research in oil & gas exploration and production. The book will benefit a broad readership, including industry experts, researchers, educators, senior engineers and managers.